A new design of a printed reconfigurable coplanar multiband antenna - Fatima Ouberri; Abdelali Tajmouati; Jamal Zbitou; Mohamed Latrach (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The demand for multi-functional components has increased enormously in recent years. Advances in integrated technology have enabled researchers to adapt diverse applications operating at different frequencies in a single wireless device. A compact broadband coplanar waveguide (CPW)-fed square aperture monopole antenna with inverted-L grounded strips is first described. The proposed antenna has a small size of 60×60×0.74 mm3 and has excellent performances which include a good input impedance matching with a much wider operating bandwidth, an excitation of the circular polarization at 2.45 GHz, and a stable omnidirectional radiation pattern. Then, a multiband reconfigurable antenna design is developed from this structure. The frequency reconfigurable approach is obtained using a varactor diode. In this work, it is observed that frequency diversity can be obtained by varying the value of the capacity by leaving the dimensions antenna unchanged. The results are given using CST microwave studio and show good performances in terms of return loss, bandwidth, gain and radiation pattern and demonstrate that the proposed antenna offers a reconfigurable solution for multi-standard wireless communication applications.